Análise das práticas psicológicas aplicadas em serviço especializado da assistência social de Manaus-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
The paper proposes an analysis of psychological practices applied by professionals at the Center for Social Assistance Specialized Reference-CREAS Manaus / AM, specifically in Protective Services and Specialized Care to Families and Individuals-PAEFI, which among other demands, serves children and adolescents victims of sexual violence. Subsidizing the analysis used the Socio-Historical perspective highlighting some elements such as culture, language, sense, meaning and subjectivity. Psychological practices corresponded to the object of research and were scored as a complex set of processes in terms of parameters of professional practice, in the context of social assistance, meets, welcomes intervenes, plans, monitors, monitors, visit reports and falls under the umbrella of a national policy and theoretical-methodological still under construction. The issue raised was the one that questioned how the parameters of performance in social psychology out of the paper and turn into psychological practice. As professionals evaluate the object under the political dimension, institutional, technical, operational and demand side of sexual violence. As for specific goals proceed with the mapping of procedures adopted by the team are based on official documents, database, covering the period from August 2009 to August 2012. We note also the opinion of professionals about the procedures applied by the service crew, interdisciplinarity and the challenges encountered. We apply the closed type questionnaires and multiple choice 08 professional reference staff and conducted semi-structured interviews with 03 psychologists. The data generated graphs, tables and a light interpretive synthesis method of interpretation of the senses. The results showed that psychological practices - despite a scenario that distorts your goals, is wrong in terms of roles and difficult to construct an identity to the "psi" assistance - to achieve its purpose of contributing to the strengthening of linkages family, in particular as regards the performance of the protective function and the broken violators of patterns within the family, repairing damage and preventing relapse. Practices are applied in order to promote the inclusion of users and families in the social protection system and existing public services, and the restoration and preservation of the integrity of users encouraging autonomy.
Keywords: Sócio-Histórica; Assistência Social; CREAS/PAEFI-AM; Práticas psicológicas; Violência sexual.; Psychological practices; Sexual violence; CIÊNCIAS HUMANAS: PSICOLOGIA